Winter habitat predictions of a key Southern Ocean predator, the Antarctic fur seal (Arctocephalus gazella). (June 2017) - Arthur, Benjamin; Hindell, Mark; Bester, Marthan; De Bruyn, P.J. Nico; Trathan, Phil; Goebel, Michael; Lea, Mary-Anne
Abstract: Quantification of the physical and biological environmental factors that influence the spatial distribution of higher trophic species is central to inform management and develop ecosystem models, particularly in light of ocean changes. We used tracking data from 184 female Antarctic fur seals ( Arctocephalus gazella ) to develop habitat models for three breeding colonies for the poorly studied Southern Ocean winter period. Models were used to identify and predict the broadly important winter foraging habitat and to elucidate the environmental factors influencing these areas. Model predictions closely matched observations and several core areas of foraging habitat were identified for each colony, with notable areas of inter-colony overlap suggesting shared productive foraging grounds. Seals displayed clear choice of foraging habitat, travelling through areas of presumably poorer quality to access habitats that likely offer an energetic advantage in terms of prey intake. The relationships between environmental predictors and foraging habitat varied between colonies, with the principal predictors being wind speed, sea surface temperature, chlorophyll a concentration, bathymetry and distance to the colony. The availability of core foraging areas was not consistent throughout the winter period. The habitat models developed in this study not only reveal the core foraging habitats of Antarctic fur seals from multiple colonies, but can facilitate the hindcasting of historical foraging habitats as well as novel predictions of important habitat for other major colonies currently lacking information of the at-sea distribution of this major Southern Ocean consumer.